1997
DOI: 10.1007/bf02051199
|View full text |Cite
|
Sign up to set email alerts
|

Colposcopic appearance of anal squamous intraepithelial lesions

Abstract: The colposcopic appearance of different grades of anal squamous intraepithelial lesions was similar to those described for the cervix. Incorporation of colposcopy into assessment of anal disease could aid in distinguishing anal LSIL from HSIL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
3
27

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(184 citation statements)
references
References 19 publications
6
148
3
27
Order By: Relevance
“…The main abnormalities associated with high-grade lesions in our patient group were dense acetowhite epithelium associated with thick punctuation or mosaic patterns. A previous study had similar findings; vascular alterations, such as punctuation and mosaics, were more frequently associated with high-grade AIN, while micropapillae and condylomata were more associated with low-grade AIN; a mosaic pattern was uncommon in low-grade lesions [12].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The main abnormalities associated with high-grade lesions in our patient group were dense acetowhite epithelium associated with thick punctuation or mosaic patterns. A previous study had similar findings; vascular alterations, such as punctuation and mosaics, were more frequently associated with high-grade AIN, while micropapillae and condylomata were more associated with low-grade AIN; a mosaic pattern was uncommon in low-grade lesions [12].…”
Section: Discussionsupporting
confidence: 63%
“…Jay found that among anuscopic findings suggestive of condyloma, 91% were really low-grade lesions at biopsy and 8% high-grade AIN [12]. These findings reinforce the importance of investigating condylomatas, because they may hide a higher-grade lesion [10,12].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Jay et al 24 utilizaram a magnificação de imagens e os parâmetros usados na colposcopia ginecológica em canal anal de 152 homens nos quais realizaram 358 biópsias. Concluíram que as imagens encontradas nos diferentes graus de neoplasias intraepiteliais evidenciadas eram similares àquelas descritas em colo uterino.…”
Section: Variáveisunclassified
“…However, the percentage of regression and progression of the lesions in these patients is unclear. 3,4 The HPV types implicated in anal intraepithelial neoplasia are similar to those described for the cervix, and it is not infrequent to observe infection by multiple types. 5 Since the prevalence of anal cancer has been increasing and the precursor conditions can be detected by screening methods, the relevance of using anal cytology and anoscopy as methods to as it leads lower rates of unsatisfactory slides.…”
Section: Introductionmentioning
confidence: 84%